The forgotten victims of war: Ukraine’s stateless - Ivashuk, A; Kordonets, S; Kanics, J (Refugee Studies Centre, University of Oxford, 2023)
War has exacerbated the severe difficulties faced by stateless people in Ukraine. Barriers to accessing humanitarian aid, safe passage and protection need to be addressed.